Bank Sharia Indonesia Strategy in Palopo City in Increasing Customer Loyalty - Salma Aulia (Journal Of Institution And Sharia Finance, 2021)
Unsatisfactory bank service will cause customers to switch to other banks, on the contrary, satisfactory bank service will make customers loyal. This study aims to determine the strategy of Indonesian Islamic banks in Palopo city in maintaining customer loyalty. this research was conducted at the Islamic Bank of Palopo city. The data collection technique is to use interviews with BSI and become informants researchers are employees and customers of BSI, documentation to collect written data. The results of this study show that the strategy used by BSI is very important through the services provided by BSI. The loyalty of customers themselves can be seen from their persistence in order to continue to use BSI services even though many other institutions offer the same product but they still survive in BSI. The quality of services provided by the bank is one of the main concerns of customers in choosing a bank.